Can You Tell the Difference? Contrastive Explanations for ABox Entailments - Koopmann, Patrick; Mahmood, Yasir; Ngonga Ngomo, Axel-Cyrille; Tiwari, Balram (Proceedings of the AAAI Conference on Artificial Intelligence)
We introduce the notion of contrastive ABox explanations to answer questions of the type “Why is a an instance of C, but b is not?”. While there are various approaches for explaining positive entailments (why is C(a) entailed by the knowledge base) as well as missing entailments (why is C(b) not entailed) in isolation, contrastive explanations consider both at the same time, which allows them to focus on the relevant commonalities and differences between a and b. We develop an appropriate notion of contrastive explanations for the special case of ABox reasoning with description logic ontologies, and analyze the computational complexity for different variants under different optimality criteria, considering lightweight as well as more expressive description logics. We implemented a first method for computing one variant of contrastive explanations, and evaluated it on generated problems for realistic knowledge bases.

Abolitionismus und Digitale Gewalt - Althoff, Sebastian (Plattformforschung nach dem Digital Services Act – Interdisziplinäre Perspektiven)

Predicting states of understanding in explanatory interactions using cognitive load-related linguistic cues - Wang, Yu; Türk, Olcay; Grimminger, Angela; Buschmeier, Hendrik (Proceedings of the 15th Language Resources and Evaluation Conference)
We investigate how verbal and nonverbal linguistic features, exhibited by speakers and listeners in dialogue, can contribute to predicting the listener's state of understanding in explanatory interactions on a moment-by-moment basis. Specifically, we examine three linguistic cues related to cognitive load and hypothesised to correlate with listener understanding: the information value (operationalised with surprisal) and syntactic complexity of the speaker's utterances, and the variation in the listener's interactive gaze behaviour. Based on statistical analyses of the MUNDEX corpus of face-to-face dialogic board game explanations, we find that individual cues vary with the listener's level of understanding. Listener states (‘Understanding’, ‘Partial Understanding’, ‘Non-Understanding’ and ‘Misunderstanding’) were self-annotated by the listeners using a retrospective video-recall method. The results of a subsequent classification experiment, involving two off-the-shelf classifiers and a fine-tuned German BERT-based multimodal classifier, demonstrate that prediction of these four states of understanding is generally possible and improves when the three linguistic cues are considered alongside textual features.

Resource-efficient universal photonic processors based on time-multiplexed hybrid architectures - Lammers, Jonas; Ares, Laura; Pegoraro, Federico; Held, Philip; Brecht, Benjamin; Sperling, Jan; Silberhorn, Christine (Physical Review Applied)
For the ever-growing field of quantum information processing, large-scale, efficient multiport interferometers serving as photonic processors are required. In this context, the suitability of quantum walks as the interferometric base for universal computation has been theoretically proven. In this work, we bridge the gap between theoretical proposals and state-of-the-art experimental capabilities by providing the recipe for the implementation of a universal photonic processor in discrete-time quantum walks. Specifically, we present the protocol for translating arbitrary linear transformations into the coin and step operator of a quantum walk and map these to the experimental parameters of the established time-multiplexed platform [A. Schreiber , Phys. Rev. Lett. , 050502 (2010)]. We show that our interface is highly scalable and resource efficient due to the hybrid encoding consisting of multiple degrees of freedom. Finally, we prove that our system is highly resilient against experimental imperfections and show that it compares favorably against existing architectures.

The Intersection Distribution: New Results and Perspectives - Klawuhn, Lukas-André Dominik; Huczynska, Sophie; Paterson, Maura (Finite Fields and Their Applications)
Intersection distribution and non-hitting index are concepts introduced recently by Li and Pott as a new way to view the behaviour of a collection of finite field polynomials. With both an algebraic interpretation via the intersection of a polynomial with a set of lines, and a geometric interpretation via a (q+1)-set possessing an internal nucleus, the concepts have proved their usefulness as a new way to view various long-standing problems, and have applications in areas such as Kakeya sets. In this paper, by exploiting connections with diverse areas including the theory of algebraic curves, cyclotomy and the enumeration of irreducible polynomials, we establish new results and resolve various Open Problems of Li and Pott. We prove geometric results which shed new light on the relationship between intersection distribution and projective equivalence of polynomials, and algebraic results which describe and characterise the degree of Sf - the index of the largest non-zero entry in the intersection distribution of f. We provide new insights into the non-hitting spectrum, and show the limitations of the non-hitting index as a tool for characterisation. Finally, the benefits provided by the connections to other areas are evidenced in two short new proofs of the cubic case.

Entangling power of nonentangling channels - Pinske, Julien; Sperling, Jan; Mølmer, Klaus (Physical Review A)

Einleitung: Die Naturlehre der Émilie Du Châtelet in Deutschland - Hagengruber, Ruth (Naturlehre)

Naturlehre - Du Châtelet, Émilie; Hagengruber, Ruth Edith

Einleitung: Alles fließt - Spener, Anna Maria (WasserWesenWandel: Fluidität in (mehr-als-)literarischen Medien. Sammelband zur fünften studentischen Tagung des Fachbereichs Komparatistik an der Universität Paderborn)

Nasses Land: Wetlands als relationale Räume gegenhegemonialer Wissensproduktion in der künstlerischen Forschung - Spener, Anna Maria (WasserWesenWandel: Fluidität in (mehr-als-)literarischen Medien)

WasserWesenWandel: Fluidität in (mehr-als-)literarischen Medien. Sammelband zur fünften studentischen Tagung des Fachbereichs Komparatistik an der Universität Paderborn

Die Grammatik des gesprochenen und geschriebenen Französisch als erste korpusbasierte Lexikogrammatik des Französischen: Grundlagen, Prinzipien, Umsetzung - Bürgel, Christoph; Siepmann, Dirk (Fremdsprachen Lehren und Lernen (FLuL), 33-48)

Modelling Deformation Mechanisms Decomposition, Separation and Compaction in Mechanical Joining Processes of Fiber Reinforced Thermoplastics on Meso Scale - Gröger, Benjamin; Gerritzen, Johannes; Hornig, Andreas; Gude, Maik (Key Engineering Materials)
The mechanical joining of continuous fiber-reinforced thermoplastics (cFRTP) and metal sheets represents a promising approach for manufacturing hybrid lightweight structures. To reduce the time and cost associated with extensive experimental investigations, numerical modeling strategies are increasingly applied. In this numerical study, a further step in the modelling strategy for the direct pin-pressing (DPP) process of cFRTP and metal sheets is presented. The study focuses on modeling and simulating the occurring deformation mechanisms of decomposition, compaction, and separation of individual rovings on the mesoscale to analyze the resulting material structure. For this purpose, two simplified models were derived. The textile architecture is represented based on micrographs of cross-sections and discretized using the finite element method. The deformation of individual rovings during joining leads to a deformation of their initial elliptical cross section. To capture this level of resolution, both a cohesive zone and a pure contact approach are applied within the rovings. The highly viscous thermoplastic melt is modeled as a fluid employing the Arbitrary Lagrange–Eulerian (ALE) method. Matrix and roving meshes are coupled to account for fluid–structure interaction (FSI) during process. The study shows that coupling of matrix and rovings is necessary to obtain more accurate predictions of the deformation behaviour. Furthermore, the cohesive zone approach is better suited to simulate the emerging deformation mechanisms.

Discounted Sales of Expiring Perishables: Challenges for Demand Forecasting in Grocery Retail Practice - Winkelmann, David; Elbracht, Theresa; Brenker, Jonas Maximilian; Gerzen, Arnold (arXiv:2602.04464)
Grocery retailers frequently apply price discounts to stimulate demand for expiring perishables. However, integrating these discounted sales into future demand forecasts presents a significant challenge. This study investigates the effectiveness of incorporating a fixed share of these sales as regular demand into the forecast, as commonly applied in practice. We employ a two-step regression approach on data from a major European grocery retailer, covering over 1,700 products across 676 stores. We reveal that forecasts underestimate actual demand for most SKUs when discounted sales occur. This residual uplift effect is significantly influenced by the number of sales at reduced prices. Our findings underscore the necessity for more precise approaches to integrate discounted sales into demand forecasts, thereby preventing excess inventory and the associated economic and environmental impacts of spoilage in the grocery sector.

An Approach for the Efficient Solution of Eigenvalue-based Inverse Problems for the Material Characterisation Using Guided Acoustic Waves - Zeipert, Henning; Claes, Leander; Hölscher, Jonas; Wippermann, Mareen; Henning, Bernd (Fortschritte der Akustik - DAGA 2026)

Simultaneous measurement of bulk and shear viscosity using guided acoustic waves - Claes, Leander (Fortschritte der Akustik - DAGA 2026)

Der christliche Hilmī Adīb, mein erster Lehrer der Koransure aḍ-Ḍuḥā - Abdelrahem, Mohammed
Keywords: religiöse Koexistenz; Religiöse Bildung; Religionsunterricht

Artificial intelligence in digital service ecosystems—Towards a taxonomy and archetypes - Hansmeier, Philipp; Schäfer, Jannika Marie; zur Heiden, Philipp (Electronic Markets)
Traditional dyadic customer-provider interactions are being shifted to polyadic interactions involving diverse participants in digital service ecosystems. Especially, artificial intelligence (AI) is increasingly integrated into these ecosystems, so that they comprise non-human participants (e.g., AI-based chatbots)—fundamentally altering the nature of value (co-)creation. While existing literature examines human-to-human interactions, knowledge of service interactions between human actors and AI-based systems is still underexplored. To address this research gap, we develop a taxonomy, comprising six iterations, that explores the peculiarities of AI as either a resource or a (non-human) agent in digital service ecosystems. We evaluate our taxonomy using a multiple case study and derive the four archetypes of AI in digital service ecosystems: (1) discriminative experience enhancer, (2) protective ecosystem orchestrator, (3) ecosystem innovation companion, and (4) personalized service composer. Our results extend the knowledge on service science by showing how AI-based systems—discriminative or generative, and focusing on the interaction in the ecosystem or the individual service encounter—assume the role of resources and non-human agents. Researchers and practitioners can utilize our results to augment their ecosystems with AI.

Towards a Service Ecosystem Perspective on Customer Experience: Insights from Hybrid (Online-Offline) Customer Journeys - Hansmeier, Philipp; zur Heiden, Philipp (Behaviour & Information Technology)

Formation of AI Anthropomorphism Structured by the Customer Journey – Towards a Conceptual Framework - Hansmeier, Philipp (Proceedings of the Thirty-Fourth European Conference on Information Systems)